Interlocução entre o procedimento de tradução de Boaventura de Sousa Santos e os preceitos da competência informacional da Ciência da Informação: um estudo de caso na área da saúde - Juliana Moreira Pinto (2018)
This work aims to analyze the interlacing of Information Science with the theoretical foundations of the translation procedure proposed by Boaventura de Sousa Santos, having as an empirical environment the promotion of informational literacy in health, through the interlocution between the professionals involved with clinical care and the patients. The purpose of this study was to evaluate whether the project for the translation of the package inserts for cardiology, carried out at the Hospital Universitário de Brasília, linked to the Universidade de Brasília (HUB/UnB), was able to preside over the preparation of leaflets that create reciprocal intelligibility among different knowledge and sociocognitive diversity - that consult them, contributing to the assertive use of medicines. Through questionnaires applied to the coordinators of the project in question, we sought to establish the general principles and rules that guided the translation work and to verify how patients participated in the preparation of the package inserts. Patients were interviewed from a health center in Belo Horizonte, with ages ranging from 18 to 88 years and schooling ranging from the 5th year of elementary education to the postgraduate course, in order to identify the degree of intelligibility of the information contained in the texts of the translated package inserts. It was concluded that the information contained in the package inserts was validated by HUB/UnB patients, who, after reading the texts, started to adhere more appropriately to the treatments proposed by the specialists of this institution and to obtain better results in relation to these treatments. The health center interviewees were able to locate the information provided in the topic of the package inserts and correctly answer questions about the use of the medicines. In view of this, it could be inferred that, in practice, the package inserts contribute to the assertive use of the drugs. The interviewees also highlighted the importance of the participation of patients in the process of elaborating the texts of the medication package inserts, since their perception and re-reading of information can contribute to a language they understand. The theoretical constructs of the translation procedure of Boaventura de Sousa Santos were considered as positive strategies to promote the interlocution of the professionals involved in health care and patients, since the information circulating between the sender and receiver could be better understood when both have a common repertoire of signs. In the area of Information Science, the theoretical foundations of the translation procedure of Boaventura de Sousa Santos reinforce the importance of the practice of information mediation between different forms of knowledge and subjects, within the scope of knowledge construction and the relations between mediation and appropriation of information, with a view to promoting informational competence and the empowerment of citizens so that they exercise citizenship and self-knowledge and coexist better in society.